Drought Stress Affecting Growth and Some Physiological Characters of Three Cocoa Clones at Seedling Phase - Fakhrusy Zakariyya; Didik Indradewa (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2018)
Drought stress can have substantial negative impacts on cocoa plant growth until affect the death of plant. The present study aimed to determine theeffect of drought stress on the some physiological characters of cacao (Theobroma cacao L.) seedlings. The research was carried out at the Indonesian Coffee and Cocoa Research Institute, Jember, East Java, Indonesia. This research was conducted from January–December 2017. The experiment was designed by using completely randomized block design with two factors and with three replications. The first factor was clones, namely ICS 60, Sulawesi 1 and KW 641 clones. The second factor was interval of watering treatment, namely watering every 2 days (control/adequate water condition), watering every 5 days (moderate stress), and watering every 8 days (severe stress). Result of this study concluded that drought stress reduced the growth of cocoa seedlings, mainly as a result of reducing photosynthetic activities in all stressed cocoa clone seedlings. Under drought stress, KW 641 and Sulawesi 1 had higher leaf area, chlorophyll a, chlorophyll b, total chlorophyll content, relative water content, and photosynthetic rate than ICS 60 clone.